A parabolic correlation between stress hyperglycemia ratio and 28-day mortality in US participants with diabetes and heart failure - Qiaowen Huang; Yonggang Peng; Lifang Xiao; Shihan Zhang; Zhiwei Lu; Huan Lin (Medicine, 2026)
Current research lacks sufficient insight into the correlation between the stress hyperglycemia ratio (SHR) and 28-day mortality in critically ill patients with heart failure and diabetes. Our study aims to investigate this correlation. A total of 1697 critically ill patients with heart failure and diabetes were enrolled from the Medical Information Mart for Intensive Care IV 3.1 database. Logistic regression, Cox proportional hazards modeling, and smooth curve fitting analyses were used to meet the research objectives. The total rate of 28-day mortality was 12.1%. Multiple regression analysis showed that the hazard ratios for 28-day mortality in the lowest (Q1), middle (Q3), and highest (Q4) SHR quartiles were 1.85 (95% confidence interval [CI] = 1.17–2.92), 1.38 (95% CI = 0.84–2.20), and 2.52 (95% CI = 1.61–3.93), respectively. Moreover, a U-shaped relationship was found between SHR and mortality risk, with the lowest risk at an SHR of 1.0. Above this level, the hazard ratio increased to 1.707 (95% CI = 1.143–2.549, P = .009). Subgroup analysis revealed no other significant findings ( P > .05). In patients with heart failure and diabetes, SHR exhibits a parabolic association with 28-day all-cause mortality. Notably, an SHR value exceeding 1.0 is associated with a significantly increased risk of 28-day mortality.